Sistem Informasi Administrasi Pengarsipan Surat - Naufal Malik Hadi Saputra; Srisulistiowati, Dwi Budi; Hadi Kusmara (Program Studi Informatika, Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2022)
SMPN 290 SMP level schools in Marunda DKI Jakarta. Based on interviews conducted with informants, there is currently no data archiving system for incoming and outgoing letters. This can lead to several aspects of error both on the part of the school and the administration, such as being effective in recording incoming and outgoing letters. To facilitate data collection ofincoming and outgoing mail, an administrative information system application was designed. With this application, this administrative information system can make it easier for the archive staff at the school and can minimize the loss and damage of letter archiving data.